Traditional Houses of the Paiwan in Taiwan: The Perspective of “House-based Societies” Reconsidered - Tan, Chang-Kou (International Journal of Environment, Architecture, and Societies, 2021)
The Paiwan, an Austronesian-speaking ethnic group, are one of sixteen Aborigines of Taiwan. This is an essay about the ethnography of traditional houses of the Paiwan. This is an essay about the ethnography of traditional houses of the Paiwan. I will describe structures, functions and construction process of traditional houses, and discuss briefly the social process and cultural meanings of houses. I have argued in an earlier paper that  the Paiwan is a ‘house-based society’, in which social and cultural reproduction are bound up with the reproduction of houses. The goal of marriage is the mission of reproduction, and the ideal conjugal relationship is the one in which the couple share a common devotion to the reproduction of the house they created. In this paper I reconsider this point of view, and I propose that the parent-child relationship and the siblingship in the family are equally important. Because the traditional houses of the Paiwan are made of stone slabs, the process of making houses is quite long. In contrast, marriage may be short-lived and fragile. Even when the marriage relationship is terminated due to divorce, the process of building and maintaining a house will not stop, and this motivation could be maintained by the parent-child relationship and the siblingship.